Estrategias de enseñanza en entornos virtuales de aprendizaje y satisfacción de las clases virtuales en estudiantes de educación inicial de la facultad de ciencias de la educación y humanidades de la Universidad Nacional de la Amazonía Peruana, Iquitos 2021 - Huaycama Yopla, Nicole Alexandra (2022)
The general objective of the research was to determine the relationship between teaching strategies in virtual learning environments and satisfaction of virtual classes in initial education students of the Faculty of Education Sciences and Humanities at the National University of the Peruvian Amazon, in Iquitos in 2021. The type of research is relational with a bivariate, cross-sectional, and field design. The study population and sample were 180 initial education students from the Faculty of Education. To obtain the data, the technique and questionnaires were used, which have previously been validated by experts. The present study concludes that Spearman's rho correlation coefficient is = 0.747 ** p = 0.000, which means that the relationship is direct, strong, and significant between the management of teaching strategies in virtual environments and the satisfaction of virtual classes in initial education students of the Faculty of Education Sciences and Humanities at the National University of the Peruvian Amazon, which also allows the verification of the hypothesis proposed for the research.